1997
DOI: 10.1063/1.119010
|View full text |Cite
|
Sign up to set email alerts
|

Nanopatterning organic monolayers on Si(100) by selective chemisorption of norbornadiene

Abstract: Norbornadiene (bicyclo[2.2.1]Hepta-2,5-diene) is shown to chemisorb selectivity at room temperature onto clean Si(100)-2×1 surfaces. Combining the chemoselectivity of this process with scanning tunneling microscope nanolithography allows the formation of nanometer-sized regions having a norbonadiene adlayer. This concept could serve as the basis for creating spatially resolved templates to initiate chemical reactions with other chemical species in the presence of hydrogen-passivated Si(100)-2×1 areas.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
34
0

Year Published

1998
1998
2012
2012

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(37 citation statements)
references
References 9 publications
3
34
0
Order By: Relevance
“…21,22 To understand this result, we have considered the energy change for a hypothetical process in which NBE approaches a fully passivated surface, displacing two gas-phase H 2 molecules as it binds to the surface. PW91 predicts that it costs 12 kcal mol Ϫ1 to complete this substitution, indicating that the reaction is thermodynamically unfavored.…”
Section: E Binding To An Incompletely Passivated Surfacementioning
confidence: 96%
See 2 more Smart Citations
“…21,22 To understand this result, we have considered the energy change for a hypothetical process in which NBE approaches a fully passivated surface, displacing two gas-phase H 2 molecules as it binds to the surface. PW91 predicts that it costs 12 kcal mol Ϫ1 to complete this substitution, indicating that the reaction is thermodynamically unfavored.…”
Section: E Binding To An Incompletely Passivated Surfacementioning
confidence: 96%
“…Some STM studies 9 have found there to be little translational or rotational order in NBE monolayers, while others 21,22 find monolayers with small regions of local order only. These studies have shown that the C-C double bonds can react with the surface in a number of ways and the binding is clearly more complex than was initially envisaged.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[206]. Copyright 2007 Elsevier B.V. [210]. It should be noted, however, that the investigation by Hovis et al published later the same year used high-coverage limit to demonstrate the lack of order in this addition process and infrared investigation to show that at least some of the norbornadiene molecules keep their double bonds intact upon adsorption on a clean Si(100)-2×1, as a pronounced ν =C-H absorption peak, characteristic of an unsaturated molecule was observed at 3057 cm −1 [209].…”
Section: Simple Derivatives Of Ethylenementioning
confidence: 97%
“…S canning tunnelling microscopy (STM) facilitates atomic-scale lithography by hydrogen resist patterning; the technique is especially useful for fundamental processes such as patterned oxidation 1 , metallization 2,3 , dopant incorporation 4 , templating of organic molecules 5,6 and fabrication of quantum cellular automata devices 7 , all at the atomic-scale. Sharpening of probes further extends to fi eld emitters 8 in displays and electron microscopes as well as razor blade manufacturing 9 .…”
mentioning
confidence: 99%